Organisational culture, leadership styles and employee’s affective commitment to change: A case of Yemen public sector - Ahmad, Hartini; Gelaidan, Hamid Mahmood (IBIMA Publishing, 2011)
The purpose of this study is to examine the effect of leadership style on the affective commitment to change, moderated by the organisational culture. The research adopts both qualitative and quantitative approaches through a survey with 371 employees of public organisations in Yemen, as well as interviews with the managers. The findings showed that the transformational leadership was positively related to the employee’s affective commitment to change; similar to the transactional leadership that was positively related to the affective commitment to change.The results showed that organisational culture had positively moderated the relationship between the leadership styles and employee affective commitment to change. Finally, the findings revealed that the transactional leadership was a strong predictor to affective commitment to change compared with the transformational leadership.